Nuclear receptor corepressor-dependent repression of peroxisome-proliferator-activated receptor delta-mediated transactivation - Krogsdam, Anne-M; Nielsen, Curt A F; Neve, Søren; Holst, Dorte; Helledie, Torben; Thomsen, Bo; Bendixen, Christian; Mandrup, Susanne; Kristiansen, Karsten (Biochemical journal, 2002)
The nuclear receptor corepressor (NCoR) was isolated as a peroxisome-proliferator-activated receptor (PPAR) delta interacting protein using the yeast two-hybrid system. NCoR interacted strongly with the ligand-binding domain of PPAR delta, whereas interactions with the ligand-binding domains of PPAR gamma and PPAR alpha were significantly weaker. PPAR-NCoR interactions were antagonized by ligands in the two-hybrid system, but were ligand-insensitive in in vitro pull-down assays. Interaction between PPAR delta and NCoR was unaffected by coexpression of retinoid X receptor (RXR) alpha. The PPAR delta-RXR alpha heterodimer bound to an acyl-CoA oxidase (ACO)-type peroxisome-proliferator response element recruited a glutathione S-transferase-NCoR fusion protein in a ligand-independent manner. Contrasting with most other nuclear receptors, PPAR delta was found to interact equally well with interaction domains I and II of NCoR. In transient transfection experiments, NCoR and the related silencing mediator for retinoid and thyroid hormone receptor (SMRT) were shown to exert a marked dose-dependent repression of ligand-induced PPAR delta-mediated transactivation; in addition, transactivation induced by the cAMP-elevating agent forskolin was efficiently reduced to basal levels by NCoR as well as SMRT coexpression. Our results suggest that the transactivation potential of liganded PPAR delta can be fine-tuned by interaction with NCoR and SMRT in a manner determined by the expression levels of corepressors and coactivators.